2009
DOI: 10.1063/1.3073887
|View full text |Cite
|
Sign up to set email alerts
|

TiN/Al Ohmic contacts to N-face n-type GaN for high-performance vertical light-emitting diodes

Abstract: We report on the electrical properties of TiN(30 nm)/Al(200 nm) Ohmic contacts to N-face n-type GaN for high-performance vertical light-emitting diodes and compare them with those of Ti(30 nm)/Al(200 nm) contacts. Both the as-deposited samples show Ohmic behaviors with contact resistivity of (6.0–7.2)×10−4 Ω cm2. However, annealing the samples at 300 °C causes the degradation of their electrical properties. Furthermore, unlike the TiN/Al contacts, the Ti/Al contacts suffer from aging degradation when exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 23 publications
3
33
2
Order By: Relevance
“…Kwak et al [10] stated that Ti/Al contact on hydride vapor phase epitaxy-grown Ga-and N-face n-GaN were annealed above 500 o C, the Ga-face showed ohmic behaviors with a ρ c of ~10 -5 Ω cm 2 , but N-face contact exhibited non-ohmic behaviors. Jeon et al [11] reported that the electrical properties of TiN/Al and Ti/Al ohmic contacts to N-face n-GaN thin films prepared by a laser lift-off process were significantly degraded upon annealing at temperatures in excess of 300 o C. These results indicate that the fabrication of high-performance vertical LEDs, low ρ c and thermally stable N-face n-ohmic contacts are essential. In this paper, we reported the Ti/Al/Pt/Au and Ti/Au ohmic contact materials on the N-face surface of oxygen doped GaN (GaN:O) substrate manufactured by Sumitomo Electric Industries.…”
mentioning
confidence: 86%
“…Kwak et al [10] stated that Ti/Al contact on hydride vapor phase epitaxy-grown Ga-and N-face n-GaN were annealed above 500 o C, the Ga-face showed ohmic behaviors with a ρ c of ~10 -5 Ω cm 2 , but N-face contact exhibited non-ohmic behaviors. Jeon et al [11] reported that the electrical properties of TiN/Al and Ti/Al ohmic contacts to N-face n-GaN thin films prepared by a laser lift-off process were significantly degraded upon annealing at temperatures in excess of 300 o C. These results indicate that the fabrication of high-performance vertical LEDs, low ρ c and thermally stable N-face n-ohmic contacts are essential. In this paper, we reported the Ti/Al/Pt/Au and Ti/Au ohmic contact materials on the N-face surface of oxygen doped GaN (GaN:O) substrate manufactured by Sumitomo Electric Industries.…”
mentioning
confidence: 86%
“…The reason for the decrease in the Ga/N ratio is that Ga is preferentially etched (or emitted) from GaN by Xe + or Kr + because the maximum elastic transferable energy of a projectile ion (Xe + or Kr + ) to a Ga target atom is higher than that of the ion to a N target atom (Ga atoms in GaN move better due to its higher elastic transferable energy from Xe + or Kr + ) based on a simple binary collision model [7,9]. This result indicates formation of Ga vacancies at the surface (or N-rich surface), creating N dangling bonds at deep levels above the valence band that trap both electrons and holes [13,14]. The Ga vacancy formation results in a decrease in the electron concentration in n-GaN, because the Ga vacancies behave as the deep acceptor-like defects [14].…”
Section: Experiments and Simulationmentioning
confidence: 84%
“…This result indicates formation of Ga vacancies at the surface (or N-rich surface), creating N dangling bonds at deep levels above the valence band that trap both electrons and holes [13,14]. The Ga vacancy formation results in a decrease in the electron concentration in n-GaN, because the Ga vacancies behave as the deep acceptor-like defects [14]. However, if N 2 molecules were formed on and then desorbed from the etched GaN surface, a different result for the Ga/N ratio would be obtained.…”
Section: Experiments and Simulationmentioning
confidence: 99%
“…Transparent conducting oxides (TCOs) are of great importance for their applications in a wide variety of devices, such as flat panel display, smart window, and optoelectronic devices (i.e., LEDs, solar cells) [1][2][3]. In order to improve the performance of such devices, TCOs should have not only high optical transparency, but also high electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%